2010
DOI: 10.1161/strokeaha.110.599464
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Single Small Subcortical Infarctions According to Infarct Location and Parent Artery Disease

Abstract: Background and Purpose-Single small subcortical infarctions (SSSIs), so-called lacunae, are typically caused by lipohyalinosis of a perforator artery. However, SSSIs can be caused by underlying large parent arterial disease or microatheroma of the proximal portion of a perforator artery. We sought to investigate whether indicators for small vessel disease (SVD) and atherosclerosis in patients with SSSI differ according to lesion location and the presence of parent artery disease. Methods-We assessed 449 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
135
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(146 citation statements)
references
References 30 publications
10
135
0
1
Order By: Relevance
“…This is particularly helpful in patients with (1) past stroke within the same vascular territory, (2) multiple small scattered infarcts within 1 arterial system, and (3) deep infarct that is suspected to have branch occlusive disease (those who have comma-shaped infarcts extending adjacent to parent artery or deep infarcts on brain stem). 70 …”
Section: Advanced Vascular Imagingmentioning
confidence: 99%
“…This is particularly helpful in patients with (1) past stroke within the same vascular territory, (2) multiple small scattered infarcts within 1 arterial system, and (3) deep infarct that is suspected to have branch occlusive disease (those who have comma-shaped infarcts extending adjacent to parent artery or deep infarcts on brain stem). 70 …”
Section: Advanced Vascular Imagingmentioning
confidence: 99%
“…Demographic characteristics and vascular risk factors, as defined by a previous study, 5 were recorded. Stroke severity was measured daily after patient admission using the National Institutes of Health Stroke Scale (NIHSS) score.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…4 On the basis of location of a MRI-identified lesion, SSIs may be classified as those extending to the surface of the MCA (proximal SSI [pSSI]) or those that do not (distal SSI [dSSI]; Figure 1A and 1B). 5 Previous studies have shown that dSSI is associated with the characteristics of small-vessel disease, including abundant microbleeds and white matter ischemic changes, whereas pSSI is more often associated with atherogenic characteristics, such as the concomitant presence of atherosclerotic cerebral vessels. 5,6 Recently, studies have reported that high-resolution MRI (HR-MRI) can show the vessel wall structure and, therefore, detect early atherosclerotic changes such as plaques, wall thickening, and arterial remodeling, even in patients with normal findings on magnetic resonance angiography (MRA).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…1,2 The causes of small subcortical infarcts in the LSA territory are highly varied and include atheroma of the parent artery, occlusion attributable to cardiogenic embolism, microatheroma arising at the orifice or proximal portion of the penetrating branch, and lipohyalinosis of the arterioles. 3,4 The infarct size often expands in the majority of cases of penetrating artery infarcts with neurological deterioration. 1,5 However, the mechanism underlying neurological deterioration and infarct volume expansion in acute small subcortical infarcts is still unknown.…”
mentioning
confidence: 99%